2010
DOI: 10.1158/1541-7786.mcr-09-0307
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Enhances S100A4 and Promotes Growth of Human Thyroid Carcinoma Cell Xenografts

Abstract: Relaxin increases cell motility and in vitro invasiveness in human thyroid carcinoma cells but the underlying molecular mechanisms of this action are largely unknown. In the present study, we show that relaxin transcriptionally upregulates the calcium-binding protein S100A4 (metastasin) and increases the cytosolic 10-kDa monomer and the 20-kDa dimer form of S100A4 in human thyroid carcinoma cells. The relaxin-induced increase in cell motility was blocked completely when S100A4 expression was diminished using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…We confirmed that treatment with relaxin induced the proliferation of cultured leiomyoma cells by up-regulating PCNA expression levels in a dose-dependent manner but not in normal myometrial cells. Our results are in accordance with reports showing that relaxin can induce proliferation of a variety of cells, including mouse uterine cervix (16), human prostate cancer (17,18), human breast cancer (19), and thyroid cancer (20). Although in mouse uterine cervix relaxin induces proliferation, we demonstrated that relaxin did not induce proliferation in human cultured normal myometrial cells but did induce proliferation in human cultured leiomyoma cells.…”
Section: Discussionsupporting
confidence: 92%
“…We confirmed that treatment with relaxin induced the proliferation of cultured leiomyoma cells by up-regulating PCNA expression levels in a dose-dependent manner but not in normal myometrial cells. Our results are in accordance with reports showing that relaxin can induce proliferation of a variety of cells, including mouse uterine cervix (16), human prostate cancer (17,18), human breast cancer (19), and thyroid cancer (20). Although in mouse uterine cervix relaxin induces proliferation, we demonstrated that relaxin did not induce proliferation in human cultured normal myometrial cells but did induce proliferation in human cultured leiomyoma cells.…”
Section: Discussionsupporting
confidence: 92%
“…Follicular thyroid cancer cells and PC-3 prostate carcinoma cells expressing RLN2 displayed enhanced xenograft growth and angiogenesis (7,69,70). The importance of the RLN/RXFP1 ligand receptor system for tumor growth is also highlighted by 2 sets of in vivo experiments.…”
Section: Discussionmentioning
confidence: 95%
“…Dewaxing, antigen retrieval and immunohistochemistry were performed as described previously (15). Sections were probed with the anti-RAGE rabbit primary antibody (1:100) or an isotype control antibody (Sigma) at equivalent protein concentrations overnight at 4⁰C.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…S100A4 gene expression has been described as a marker for poor prognosis in patients with TC (10), serves as an early marker for metastasis in PTC, including papillary microcarcinomas, and correlates with invasiveness in FTC (11)(12)(13). Our group has previously shown that S100A4 production is significantly enhanced by Relaxin/RXFP1 and INSL3/RXFP2 signaling in human TC cells (14,15) and that S100A4 mediates the pro-migratory effects induced by these peptides in TC cells.…”
Section: Introductionmentioning
confidence: 97%